THE CORRELATION BETWEEN FREQUENCY OF VISITING LIBRARY AND THE STUDENTS’ INTEREST IN LEARNING AT SMK SETIA BUDI BINJAI - Syafrida Hafni; Rina Irawan Nasution; Raja Aminuddin Siregar; Saimarlina Harahap; Musthafa Haris Munandar (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Basically, process of studying is not only done in the classroom, but in the library as well. Library is one of the most essential tools of learning to help student in getting of reading source. Because it contains many scientific book and references. There are also many books available in the library whose purpose is to increase students' interest in learning. With frequent students reading in the library, it will increasingly have a positive influence on student learning interest. This research was conducted to find out: The students’ frequency in visiting library, the students’ interest in learning English, and the significant correlation between frequency of visiting library and the students’ interest in learning English. The population in this study, I took all students from SMK Setia Budi Binjai in the 2009/2010 academic year as many as 281 students in 7 classes, and the total sample was 74 students, to get the data, I use the torayame formula, through questionnaires and interviews. students were asked to answer these questions, then in analyzing the data I used the ramus product moment. The results of that analysis, (1) the students’ frequency in visiting library can be seen in mean of it, that is 6,92 with the standard deviation is 48, 00, (2) the students’ interest in learning can be seen mean of it that is 6,25 with the standard deviation is 39, 12, (3) the value of correlation product moment is 0,541 while it 0,227 at 2 = 0,005, it means that ro > rt (0,541 > 0, 227). So that, the hypothesis (Ho) was rejected, it means that there is positive correlation between frequency of visiting library and the students’ interest in learning English.